Vivendo o espaço urbano: sociabilidade e apropriações no cotidiano da Praça do Caju em João Pessoa PB - Campos, Ricardo Bruno Cunha (2010)
The present work treats of the sociability and urban culture thematics and the public spaces configuration in brazilian society, based on the individuals quotidian practices and actions that build these spaces. The work discusses the sociability and the social appropriations in the Praça do Caju (Cashew Square) located in the district of Bessa, João Pessoa, Paraíba (Brazil), focusing, as main aspect, the relations among their users and how they activate the local cultural processes. By means of their actions, memories and constitution in the historic process, it was established a dialogue with the symbolic, structural and socioeconomic informations that impel them to these living experiences. The objective was to examine the construction and the maintenance of the public space, both in the social as in the imaginary of contemporary brazilian cities inhabitants, as well as the cultural processes of appropriations and uses that comprise, establish and reconfigurate the sociabilities of specific public spaces involved in the development of the city. A ethnographic research was fundamental in order to clearfy the local urban development, establishing the specificity of a square situated in a midle class district and also elucidate the material and symbolic strategies that make possible life and the living in a society where the social inequality is reflected in elements as: space segregation, stigma, the public use and appropriation, and the belonging to a group and places inside of it.